2019
DOI: 10.1093/jn/nxz020
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of 46 Studies Identified by the FDA Demonstrates that Soy Protein Decreases Circulating LDL and Total Cholesterol Concentrations in Adults

Abstract: Background Certain plant foods (nuts and soy protein) and food components (viscous fibers and plant sterols) have been permitted by the FDA to carry a heart health claim based on their cholesterol-lowering ability. The FDA is currently considering revoking the heart health claim for soy protein due to a perceived lack of consistent LDL cholesterol reduction in randomized controlled trials. Objective We performed a meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 74 publications
1
45
0
1
Order By: Relevance
“…Soy protein is extensively consumed worldwide, and its consumption has been associated with an improvement of several metabolic alterations, including a reduction in total and LDLcholesterol and triglycerides, and also an improvement of insulin sensitivity. [36,37] Several studies using tools of nutrigenomics have demonstrated that consumption of soy protein reduces de expression of lipogenic genes and increases the expression of genes of the fatty acid oxidation. As a consequence, there is a reduction in the development of fatty liver in several animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Soy protein is extensively consumed worldwide, and its consumption has been associated with an improvement of several metabolic alterations, including a reduction in total and LDLcholesterol and triglycerides, and also an improvement of insulin sensitivity. [36,37] Several studies using tools of nutrigenomics have demonstrated that consumption of soy protein reduces de expression of lipogenic genes and increases the expression of genes of the fatty acid oxidation. As a consequence, there is a reduction in the development of fatty liver in several animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Among this OC sample, both FFQ and 7-d FR data provided evidence of some potentially beneficial changes in dietary composition in relation to MDE restriction, such as small but significant increases in non-soya legumes, soya products, and nuts and seeds. Including more of these foods in the diet may help reduce blood lipid levels and improve glycaemic control (45)(46)(47)(48)(49)(50) , though such benefits would arguably depend on baseline diet and on which foods the nuts, seeds, legumes and soya products displace. It is unclear whether the approximately 0•09-serving increase in legumes observed in this sample in relation to 1-serving decrease in MDE products would have a substantial effect on blood lipids or glucose control, especially considering that approximately one-third of strict MDE fasters were still not meeting national guidelines on weekly legume consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Later, in 2006, the American Heart Association (AHA) reported a modest effect of soy foods on LDL cholesterol: a reduction by approximately 3%, and stated that the benefit was very small relative to the large amount of soy protein tested, which averaged 50 g per day, about half the usual total daily protein intake . Recently, a meta‐analysis of 46 studies identified by the FDA demonstrates that soy protein decreases circulating LDL, by approximately 3–4%, and total cholesterol concentrations in adults . The mechanism responsible for the plasma cholesterol reduction remains an open question .…”
Section: Discussionmentioning
confidence: 99%